LEFT VENTRICULAR DIASTOLIC FUNCTION IN RELATION TO SODIUM DIETARY INTAKE AND RENAL HANDLING. (June 2018) - Wojciechowska, W.; Stolarz-Skrzypek, K.; Olszanecka, A.; Bednarski, A.; Barton, H.; Folta, M.; Kawecka-Jaszcz, K.; Czarnecka, D.
Abstract : Objective: Sodium load has been associated with blood pressure (BP) and target organ damage. Sodium sensitivity of BP varies between individuals and may be determined by renal sodium handling. The present study aimed to investigate ambulatory blood pressure and left ventricular diastolic function in relation to interaction between sodium dietary intake and renal handling. Design and method: We recruited 303 (mean age, 46.9 years; 55% women) members from randomly selected families. The 24-hour blood pressure monitoring was assessed. Left ventricular mass index, left atrium (LA) diameter, and the ratio of early (E) and late (A) diastolic peak of transmitral flow velocities (E/A) as well as the ratio of E to tissue doppler early diastolic mitral annular velocity (Em) were assessed by echocardiography (VIVID 7). Serum and urinary sodium concentration was measured using an automatic analyzer while lithium concentration by automatic absorption spectrometry. The median value of urinary sodium excretion (uNa) and median value of fractional urinary lithium excretion (FELi) - marker of sodium reabsorption in proximal tubules and as a consequence sodium sensitivity - were calculated. Results: To evaluate the influence of high sodium diet on parameters of interest we divided participants on two groups: high sodium group (HNa) constituted 86 participants with uNa above the median value (156.6 mmol/day) and FELi below the median value (16.6%), while the low sodium group (LNa) combined 79 persons with uNa below and FELi above the respective median value. 24-hour systolic and diastolic BP, left atrium diameter and E/Em were higher in HNa group in comparison to LNa participants (p < 0.05). After adjusting for relatedness, age, gender, and antihypertensive treatment, significant differences between predefined groups in 24-hour systolic BP (120.2 vs 117.0 (mmHg), p = 0.03) and E/Em (7.3 vs 6.7(%), p = 0.016) ratio persisted. Conclusions: The study may be the basis for an assumption that in participants with a paradoxical high renal sodium retention in case of sodium overload an impairment of cardiac diastolic function develops sooner, suggesting that a reduction of salt intake may improve cardiac diastolic function.